2004
DOI: 10.1128/aac.48.9.3498-3507.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Emergence of Entecavir-Resistant Hepatitis B Virus Requires Additional Substitutions in Virus Already Resistant to Lamivudine

Abstract: Entecavir (ETV) exhibits potent antiviral activity in patients chronically infected with wild-type or lamivudine (3TC)-resistant (3TC r ) hepatitis B virus (HBV). Among the patients treated in phase II ETV clinical trials, two patients for whom previous therapies had failed exhibited virologic breakthrough while on ETV.Isolates from these patients (arbitrarily designated patients A and B) were analyzed genotypically for emergent substitutions in HBV reverse transcriptase (RT) and phenotypically for reduced sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
492
4
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(516 citation statements)
references
References 31 publications
18
492
4
2
Order By: Relevance
“…None of these 13 patients experienced an ALT flare in association with the virologic breakthrough. Previous studies have shown that among patients harboring lamivudine-resistance mutations rtL180M and rtM204V, an additional substitution at residue rtT184, rtS202, or rtM250 may be associated with reduced susceptibility to entecavir [25]. Genotypic analyses on paired baseline and on-treatment samples from the 13 patients in the current study found no emerging substitutions at residues rtT184, rtS202, or rtM250, suggesting that the observed virologic breakthroughs were not due to the emergence of genotypic resistance to entecavir.…”
Section: Resistancesupporting
confidence: 49%
See 2 more Smart Citations
“…None of these 13 patients experienced an ALT flare in association with the virologic breakthrough. Previous studies have shown that among patients harboring lamivudine-resistance mutations rtL180M and rtM204V, an additional substitution at residue rtT184, rtS202, or rtM250 may be associated with reduced susceptibility to entecavir [25]. Genotypic analyses on paired baseline and on-treatment samples from the 13 patients in the current study found no emerging substitutions at residues rtT184, rtS202, or rtM250, suggesting that the observed virologic breakthroughs were not due to the emergence of genotypic resistance to entecavir.…”
Section: Resistancesupporting
confidence: 49%
“…Entecavir's potent suppression of viral replication and high genetic barrier helps to minimize the emergence of virologic resistance. Tenney and coworkers have shown that resistance to entecavir requires the presence of lamivudine-resistance mutations rtL180M and/or rtM204V plus additional substitution in the HBV reverse transcriptase at positions rtT184, rtS202, or rtM250 [25]. In this study, there was no evidence of emerging substitutions associated with virologic resistance to entecavir.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…To date, a limited number of ETV‐resistant mutations have been reported. They include the LAM‐resistant‐associated amino acid mutations at rt180 and rt204 and require additional mutations at rt169, rt184, rt202, or rt250 8, 12. Mutations of rtI163V and rtA186T in addition to the LAM‐resistant mutations have been reported to confer ETV resistance 13…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ETV, it has been reported that resistance to the drug requires at least one of three substitutions in HBV RT, that is, rtT184, rtS202, and rtM250, as well as LVDr-related substitutions rtL180M and M204V [24]. Phenotypic analyses of samples associated with virologic breakthrough confirmed that ETV susceptibility correlates with the spectrum of these additional substitutions conferring genotypic resistance and the increased level of circulating HBV DNA [25].…”
Section: Discussionmentioning
confidence: 94%